Star Trek. Section 31 [videorecording (DVD)] - Sweeny, Craig, 1973-; Kim, Bo Yeon; Lippoldt, Erika; Yeoh, Michelle, 1962-; Hardwick, Omari, 1974-; Richardson, Sam (Actor); Kazinsky, Rob, 1983-; Rohl, Kacey; Ruygrok, Sven; Liao, James Hiroyuki; González, Humberly; Pingue, Joe; et al. (CBS, 2025)
Emperor Philippa Georgiou joins a secret division of Starfleet. Tasked with protecting the United Federation of Planets, she also must face the sins of her past.